Ce alpha Mn1-alpha O2 CATALYSTS SUPPORTED OVER gamma-Al2O3 PREPARED BY MODIFIED REDOX-COPRECIPITATION METHODS FOR n-HEXANE COMBUSTION - Rojas Quispe, Jesus (2020)
A series of Ce alpha Mn1-alpha O2 catalysts supported on gamma-alumina with various molar concentrations of Ce (alpha, from 0 to 0.90) was synthesized by coprecipitation, applying two different precipitating agents, namely, sodium hydroxide (method 1) and sodium carbonate (method 2), with the use of sodium permanganate as a redox agent for precipitation. XRD profiles of the supported samples revealed the predominant abundance of a typical fluorite crystalline structure. TPR thermograms of supported samples were displaced towards lower temperatures with increasing Mn concentration, in contrast with the bulk samples. The supported Ce-Mn samples exhibited a greater performance in n-hexane elimination than did the corresponding simple oxides. The sample Ce0.33M O-0.67(2) obtained by method 2 presented the best activity, probably due to the enrichment of Ce4+, Mn3+ and Mn4+ surface species, an excess of superficial oxygen species and an easy reducibility as well as the lowest apparent activation energy.